Implementation of Information Technology for the Indonesian Navy in Dealing with Cyber Threats - Syahlan, Zainal (IJOSMAS, 2023)
National defence in the seas faces increasingly complex challenges due to developments in information technology. Cyber threats are a significant threat to national security, including in the context of national defence at sea. Therefore, the Indonesian Navy as a component of national defence needs to apply sophisticated information technology to deal with this threat. This study aims to analyse the application of Indonesian Navy information technology in dealing with cyber threats to support national defence at sea. The method used in this study is a qualitative method with a case study approach. This research involved collecting data through in-depth interviews, participant observation, and analysis of related documents. The results of this study indicate that the Indonesian Navy has implemented various innovative information technologies to deal with cyber threats. The application of this information technology involves Information Technology Infrastructure (hardware), the readiness of the Required Cyber Operation Software and Human Resources (brain ware), as well as the development of cyber capabilities within the organization. Through the application of this information technology, the Indonesian Navy can support national defence at sea more effectively